Concomitant temporary mechanical support in high‐risk coronary artery bypass surgery. Issue 12 (26th October 2019) - Ranganath, Neel K.; Nafday, Heidi B.; Zias, Elias; Hisamoto, Kazuhiro; Chen, Stacey; Kon, Zachary N.; Galloway, Aubrey C.; Moazami, Nader; Smith, Deane E.
Abstract: Objectives: Patients with low left ventricular ejection fraction (LVEF) undergoing high‐risk coronary artery bypass grafting (CABG) are at increased risk for postcardiotomy cardiogenic shock. This report describes planned concomitant microaxial temporary mechanical support (MA‐TMS) device placement as a viable bridge‐to‐recovery strategy for high‐risk patients receiving surgical revascularization. Methods: A retrospective review was performed for all patients from October 2017 to May 2019 with low LVEF (<30%), New York Heart Association Class III or IV symptoms, and myocardial viability who underwent CABG with prophylactic MA‐TMS support at a single institution ( n = 13). Results: Mean patient age was 64.8 years, and 12 patients (92%) were male. Eight patients (62%) presented with acute coronary syndrome. Mean predicted risk of mortality was 4.6%, ranging from 0.6% to 15.6%. An average of 3.4 grafts were performed per patient. Greater than 60% of patients were extubated within 48 hours and out‐of‐bed within 72 hours, and the average duration of MA‐TMS was 5.7 days. Mean postoperative length of stay was 16.7 days. There were no postoperative myocardial infarctions or deaths. Conclusions: Prophylactic MA‐TMS may allow safe and effective surgical revascularization for patients with severe left ventricular dysfunction who may otherwise be offered a durable ventricular assist device.